Mesoscale modelling of dynamic porosity in cement hydrate gel during a water sorption cycle: A lattice Boltzmann study. (August 2021) - McDonald, Peter J.; Borg, Miryea N.; Faux, David A.
Abstract: We describe a lattice Boltzmann modelling framework for fluid sorption coupled to a dynamic model of cement hydrate microstructure upon which it is possible to explore ideas of water sorption in cement emergent from NMR and other recent experimental studies. The results of the first simulations using the model are presented. We show that it is possible to extract transport and microstructural relaxation parameters from the simulations that are in good qualitative agreement with experiment. We discuss limitations of the methodology.